IMPROVING STUDENT™S ACHIEVEMENT IN WRITING NARRATIVE PARAGRAPH THROUGH PICTURES - Purba, Ruth Ganda Juliana (Universitas Negeri Medan, 2014)
Abstract This study deals with an attempt to improve students™ achievement in writing narrative paragraph through pictures. This study was conducted by using classroom action research. The subject of the research was class XI IPA of SMA Swasta Gajah Mada consisting of 32 students. The data for the research were writing test as the quantitative data and diary notes, observation sheet, interview sheet and questionnaire sheet. Based on the writing tests, students™ scores kept improving in every test. In the first cycle, the mean score was 53,18. In the second test the mean score was 64,87, and in the third test the mean score was 72,5. Based on diary notes, observation sheet and questionnaire sheet and interview sheet, it was found that students were actively involved in writing process as the response to the applied media pictures. The result of the research showed that pictures can improve students™ achievement in writing narrative paragraph. Keywords: Writing, Narrative Paragraph, Picture